Between Sigmund Freud and Paul Federn: culture as a shared path of sublimation. Issue 1 (2nd January 2016) - Houssier, F.; Blanc, A.; Bonnichon, D.; Vlachopoulou, X.
ABSTRACT: Freud's interest in culture and its various manifestations – one could even call it a passion of his – is well known. We examine the correspondence between Freud and Paul Federn – which consists of 147 cards and letters, some of them completely new, and includes Freud's letters to Federn's wife – in order to show that their relationship too was based on their shared interest in culture. Federn was more than a colleague: he was both Freud's right-hand man institutionally in Vienna and a trusted person to whom he referred some of his patients. This correspondence has not only historical significance but also brings to light the theoretical stakes in issues that continue to remain central to psychoanalysis.